Slow Boiling the Economic Frog: A Historical Perspective on Offshoring - Muczyk, Jan (Journal of Comparative International Management, 2007)
The “Theory of Comparative Advantage” has been used to justify international trade and offshoring. However, the theory is predicated on the immobility of factors of production, and that no longer is the case. The world-wide fiber optic network creates a superhighway to all the workforces of the world for all jobs or parts of jobs that can be digitized. While consumers, some investors, and some executives profit from offshoring, many jobs, especially manufacturing, are lost, and they will not be replaced by high tech jobs created by an innovative and flexible economy. Hence, recommendations have been advanced to create greater import/export parity, even if it means higher prices and more inflation.